DIAGNOSIS AND TREATMENT OF STATUS EPILEPTICUS : AN UPDATE SYSTEMATIC REVIEW - Husna, Asmaul; Annisa Hasanah, Sarah (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Status epilepticus (SE) is a condition resulting from the failure of the mechanisms involved in termination or the initiation of mechanisms responsible for seizure prolongation. The aim: The aim of this study to show about diagnosis and treatment of status epilepticus. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 110 articles, whereas the results of our search on SagePub get 163 articles, on Google Scholar 8200 articles. Records remove before screening are 7182, so we get 2761 articles fos screening. After we screened based on record exclude, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: There are increasingly more drug options to treat SE, but rational polytherapy should consider the pharmacodynamics and kinetics of established and new antiepileptic drugs. When seizures cannot be controlled with conventional medical therapy, non-conventional treatments, including early surgical evaluation can be considered; however, high-quality evidence for these strategies are lacking. Neurointensivists are challenged to reduce secondary brain injury by managing common complications.